The early clarinet : a practical guide - Lawson, Colin (Colin James) (Cambridge handbooks to the historical performance of music., 2000)
This guide is intended for all clarinettists with a desire to investigate music of earlier periods. It contains practical help on both the aquisition and playing of historical clarinets, while performers on modern instruments will find much advice on style, approach and techniques which make up a well-grounded, period interpretation.